Noninvasive Transcutaneous Monitoring in Long-Term Follow-Up of Patients With Thromboangiitis Obliterans Treated With Intravenous Iloprost. (July 2015) - Melillo, Elio; Grigoratos, Chrysanthos; Sanctis, Francesco De; Spontoni, Paolo; Nuti, Marco; Dell'Omodarme, Matteo; Ferrari, Mauro; Balbarini, Alberto
We evaluated the effectiveness of intravenous iloprost (IVI) in outpatients with thromboangiitis obliterans (TAO) and lower limb noninvasive transcutaneous monitoring (TCM) at follow-up (FU). Ten consecutive patients with TAO underwent IVI therapy. Transcutaneous oxygen (TcPo 2 ) and carbon dioxide (TcPco 2 ) determination and laser Doppler flowmetry (LDF) were performed before and after IVI at 3, 6, and 12 months of FU. Clinical response was positive in 7 patients, whereas 3 nonresponders underwent a second IVI cycle with 1 showing a late positive clinical response. After 12 months of FU, all patients were alive without amputations. Supine and dependent TcP2 levels significantly improved ( P < .005). Hallux LDF values showed significant change with the maximal hyperemic test at 44°C ( P < .005). Forefoot maximal hyperemic test at 44°C LDF ( P < .005) and improved venous arterial reflex ( P < .05) showed statistically significant time evolution. We demonstrated some degree of IVI effectiveness and evaluated TCM in patients with TAO.